Egg Production, Egg Quality, and Fatty Acid Profile of Indonesian Local Ducks Fed with Turmeric, Curcuma, and Probiotic Supplementation - I. Ismoyowati; D. Indrasanti; A. Ratriyanto; Sumiati (Faculty of Animal Science, Bogor Agricultural University, 2022)
Indonesian local ducks are commonly raised for egg production purposes. However, the performances of these ducks are still variable and must be improved. This study investigated the effects of turmeric, curcuma, and probiotic supplementations on the egg production and quality of Indonesian local ducks, emphasizing the eggs’ fatty acid profile. Two hundred female local ducks aged 16 weeks were randomly allotted to four dietary treatments with five replicates of 10 birds. The ducks were fed a corn and rice bran-based diet containing different supplements, i.e., a diet without supplementation as the control diet, a diet supplemented with turmeric at the level of 4%, a diet supplemented with curcuma at the level of 4%, and a diet supplemented with starbio probiotics at the level of 2%. The measured data were analyzed using analysis of variance using the 13 Systat program and continued with Duncan’s Multiple Range Test. Turmeric supplementation increased egg production compared with the control, and the duck fed probiotics consumed more feed than the control. Curcuma supplementation generated the lowest feed consumption, egg production, and physical egg quality than the other treatments (p<0.05). The probiotics supplementation enhanced the blood high-density lipoprotein concentration (p<0.05). Turmeric, curcuma, and probiotics supplementations generate variable responses in egg production and egg quality, including the fatty acid profile in the eggs. Turmeric and probiotics supplementations positively impact egg production, egg quality, or unsaturated fatty acid profile in the egg. However, curcuma supplementation decreased egg production and egg quality of local ducks. Furthermore, the fatty acid profile was not influenced by these supplements. It is concluded that supplementation of turmeric at the level of 4% and probiotics at the level of 2% in the diet can increase egg production and egg quality of local duck.